2019
DOI: 10.2147/ccide.s183981
|View full text |Cite
|
Sign up to set email alerts
|

<p>Oral health in patients with Prader-Willi syndrome: current perspectives</p>

Abstract: Prader-Willi syndrome (PWS) is a rare complex multisystem disorder and presents several aspects related to dentistry. The purpose of this review is to present current perspectives about oral health in patients with PWS. Delay development, hyperphagia, foamy and highly viscous saliva raise the risk of caries and contribute to tooth wear. Cariogenic foods uncontrolled consumption allows to obesity and dental problems progress worsening systemic disorders. These factors can be controlled. The success in follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
5
0
2
Order By: Relevance
“…Estos hábitos alimenticios son similares a los observados en pacientes con SPW. 17 En una revisión sistemática publicada en 2017, He et al 5 sugieren que la causa principal asociada con la obesidad en la infancia y la adolescencia es el alto consumo de calorías. Byrne et al (2019) mostraron que la pérdida de peso es más efectiva cuando se reduce esta ingesta.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estos hábitos alimenticios son similares a los observados en pacientes con SPW. 17 En una revisión sistemática publicada en 2017, He et al 5 sugieren que la causa principal asociada con la obesidad en la infancia y la adolescencia es el alto consumo de calorías. Byrne et al (2019) mostraron que la pérdida de peso es más efectiva cuando se reduce esta ingesta.…”
Section: Discussionunclassified
“…3 También se observan mayor prevalencia de malformaciones dentales y mayor incidencia de afecciones periodontales, xerostomía, y desgaste dentario pronunciado. 4,5 En otras investigaciones se observó mayor prevalencia de caries, erosión del esmalte y maloclusión en comparación con la población sin SPW. 6 El presente estudio tuvo como objetivo evaluar el estado de salud bucal y el crecimiento craneofacial en pacientes con SPW a través de la evaluación clínica y radiográfica, en comparación con los niños no obesos con SPW.…”
Section: Introductionunclassified
“…These include disorders of saliva secretion (DS; Prader Willi syndrome (PWS)), malocclusion (SLOS; DS. ; SRS; Angelman syndrome (AS)), crowding of the teeth, enamel developmental disorders (SLOS; DS; SRS; AS), muscle hypotonia and mouth breathing (SLOS; PWS), tongue dysfunction (DS), bruxism (PWS), gastroesophageal re ux (SLOS; PWS), immune de ciency (DS) [6][7][8][9]. Many of the aforementioned factors can be controlled by paying attention to oral hygiene, proper nutrition and continuous dental care from birth to adulthood [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the well-studied gut microbiome, characterization of salivary microbiota composition and biodiversity have not yet been explored in PWS populations despite that the oral microbiome has been recognized as potential key biomarkers of several oral and systemic diseases that may be related to symptoms of PWS [14]. For example, PWS patients were found to have high rate of oral diseases such as caries and tooth wear due to developmental delay, hyperphagia, and thick saliva [15]. As the human salivary microbiota is comprised of highly diverse groups of commensal, symbiotic, and pathogenic microorganisms, current research has suggested that such influences of the salivary microbiota extend beyond that of the oral cavity [16].…”
Section: Introductionmentioning
confidence: 99%